Phosphorus fertilisation and large legume species affect jarrah forest restoration after bauxite mining - Daws, Matthew; Standish, R.; Koch, J.; Morald, T.; Tibbett, M.; Hobbs, R. (Elsevier, 2015)
© 2015 Elsevier B.V. Re-establishing nutrient-cycling is often a key goal of mine-site restoration. This goal can be achieved by applying fertilisers (particularly P) in combination with seeding N-fixing legumes. However, the effect of this strategy on other key restoration goals such as the establishment and growth of non-leguminous species has received little attention. We investigated the effects of P-application rates either singly, or in combination with seeding seven large understorey legume species, on jarrah forest restoration after bauxite mining. Five years after P application and seeding, legume species richness, density and cover were higher in the legume-seeded treatment. However, the increased establishment of legumes did not lead to increased soil N. Increasing P-application rates from 0 to 80kgPha-1 did not affect legume species richness, but significantly reduced legume density and increased legume cover: cover was maximal (~50%) where 80kgPha-1 had been applied with large legume seeds. Increasing P-application had no effect on species richness of non-legume species, but increased the density of weeds and native ephemerals. Cover of non-legume species decreased with increasing P-application rates and was lower in plots where large legumes had been seeded compared with non-seeded plots. There was a significant legume×P interaction on weed and ephemeral density: at 80kgPha-1 the decline in density of these groups was greatest where legumes were seeded. In addition, the decline in cover for non-legume species with increasing P was greatest when legumes were seeded. Applying 20kgPha-1 significantly increased tree growth compared with tree growth in unfertilised plots, but growth was not increased further at 80kgha-1 and tree growth was not affected by seeding large legumes. Taken together, these data indicate that 80kgha-1 P-fertiliser in combination with (seeding) large legumes maximised vegetation cover at five years but could be suboptimal for re-establishing a jarrah forest community that, like unmined forest, contains a diverse community of slow-growing re-sprouter species. The species richness and cover of non-legume understorey species, especially the resprouters, was highest in plots that received either 0 or 20kgha-1 P and where large legumes had not been seeded. Therefore, our findings suggest that moderation of P-fertiliser and legumes could be the best strategy to fulfil the multiple restoration goals of establishing vegetation cover, while at the same time maximising tree growth and species richness of restored forest.